APLIKASI ARSITEKTUR EKOLOGIS PADA PERANCANGAN BALAI BESAR PELATIHAN PERTANIAN BAWANG MERAH DI NGANJUK - Ogif Ratuanar; Agus Heru Purnomo; Ana Hardiana (Universitas Sebelas Maret Surakarta, 2017)
Design of Shallot Agricultural Training Center in Nganjuk starts from the potential of shallot farming with abundant crops. Many of the farmers who want to develop more knowledge about shallot , not just local farmers but also from other regions. This region need a space of agricultural education activities that can accommodate a variety of agricultural training especially in shallot farming,. With the approach of ecological architecture that pay attention to natural factors such as: climate, ecological materials and health of its users. The result of planning with ecological design strategy will result in space of activity which suited to need and environmentally friendly building area.Keywords: Trainning center, Shallot, Nganjuk, Ecology